Optofluidics 2015 - Yi-Chung Tung (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Optofluidics combines and integrates optics and fluidics to produce versatile systems that are achievable only with difficulty through either field alone. With the spatial and temporal control of the microfluids, the optical properties can be varied, providing highly flexible, tunable, and reconfigurable optical systems. Since the emergence of optofluidics, numerous systems with varied configurations have been developed and applied to imaging, light routing, bio-sensors, energy, and other fields. This Special Issue aims to collect high quality research papers, short communications, and review articles that focus on optofluidics, micro/nano technology, and related multidisciplinary emerging fields. The special issue will also publish selected papers from the 5th Optofluidics 2015 conference (http://www.optofluidics2015.org/), 26-28 July 2015, Taipei, Taiwan. The aim of optofluidics 2015 conference is to provide a forum to promote scientific exchange and to foster closer networks and collaborative ties between leading international optics and micro/nanofluidics researchers across various disciplines. The scope of Optofluidics 2015 is deliberately broad and interdisciplinary, encompassing the latest advances and the most innovative developments in micro/nanoscale science and technology. Topics range from fundamental research to its applications in chemistry, physics, biology, materials and medicine.